Leguminosae nodulating bacteria diversity from three different land use systems in Brazilian Western Amazon - Jesus, Ederson da Conceição; Moreira, Fátima Maria de Souza; Florentino, Ligiane Aparecida; Rodrigues, Maria Isabel Dantas; de Oliveira, Marcelo Silva (Pesquisa Agropecuaria Brasileira, 2005)
<!–[if gte mso 9]> Normal 0 <![endif]–> <!– /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:PT-BR; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> The aim of this work was to evaluate the effect of three different land use systems from the Brazilian Western Amazon on Leguminosae nodulating bacteria diversity. The land use systems studied were cassava crop, peach palm crop and upland forest. Rhizobial densities were evaluated by the most probable number technique, after inoculation of Macroptilium atropurpureum with diluted soil samples, and they were similar for the three systems studied. Two hundred and fifty-seven bacteria isolated from the nodules were characterized and clustered into 63 groups of isolates with 80% similarity. Few isolates were obtained from forest, whereas a large number of isolates was obtained in the crop systems. The highest richness and Shannon diversity were found in the cassava crop and the lowest ones were found in the forest. However, the richness was similar for the three systems when it was determined with a rarefaction analysis. Differences in the proportion of types of growth were found and can be explained by differences amongst the systems. The land use systems influenced the Leguminosae nodulating bacterial diversity.